Growth Evaluation of Some Dipterocarp Species in Revegetation Areas of PT. Kitadin, East Kalimantan - Iwan Hilwan; Yadi Setiadi; Hendriyana Rachman (Jurnal Silvikultur Tropika, 2013)
The existence of dipterocarp species is very important especially in lowland tropical rain forest. Dipterocarp species has high economical and ecological values. Borneo is one of the region dipterocarp species. Logging has resulted in the decrease of dipterocarp species, moreover, mining industry has worsen this condition. According to IUCN (International Union for Conservation of Nature), that these kinds of plants have been categorized endangered. PT Kiadin in collaboration with Research Center of Dipterocarp Samarinda performed planting trials of various dipterocarp. The experiment was carried out in 2009 in the area of pre-conditioned post-mining area. The planting was done in five locations that had previously been planted with pioneer tree species in which each location had different types of shading. In order to know which dipterocarp species that is the most superior and in which locations these species existed, the growth of several types of dipterocarp in post-mining landscapes of PT. Kitadin was evaluated. This study aimed to identify which types of dipterocarp species that grew the best in various locations of revegetation of PT. Kitadin. Based on the research done, there was a tendency that five dipterocarp species grow well in the shade of waru. However, precentage of these five dipterocarp species life was mostly under the shade of trembesi. Parashorea smythiesii species had greater average height, diameter, and survival rates than those of other species. Thus, this species is a potential species that could be used too planting in the ex mine siter of PT. Kitadin.Key words: dipterocarp, growth evaluation, revegetation